Implementasi Sistem Penjualan Pada Berbasis Aplikasi - Baidowi, Ahmad; Yakob, Galih Satria; Barronzoeputra, Gaoeng Qalbun; Fahmi, Hakon; Sarimole, Frencis Matheos (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
Businesses today benefit greatly from information technology, especially in creating computer-based applications, websites, and sales information systems. This technology allows for quick and easy sales data management and buy-sell transactions. This system can process sales transaction data efficiently, which allows precise and fast information reports to be generated. By creating an application, Warkuy Cafe, located in Bekasi City, overcomes the problem of manual sales data recap. This system aims to increase the convenience, attractiveness, and efficiency of online services and ordering. These applications include information about sales transactions, delivery messages, booking order systems, and e-wallet payments. Software such as Learning Management System (LMS) and Content Management System (CMS), which help users and administrators edit data, created the applications. This innovation enhances Warkuy Cafe's operations and improves customers' shopping experience.